2017
DOI: 10.1002/adfm.201605164
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous Tenfold Brightness Enhancement and Emitted‐Light Spectral Tunability in Transparent Ambipolar Organic Light‐Emitting Transistor by Integration of High‐k Photonic Crystal

Abstract: In organic light-emitting transistors, the structural properties such as the in-plane geometry and the lateral charge injection are the key elements that enable the monolithic integration of multiple electronic, optoelectronic, and photonic functions within the same device. Here, the realization of highly integrated multifunctional optoelectronic organic device is reported by introducing a high-capacitance photonic crystal as a gate dielectric into a transparent single-layer ambipolar organic light-emitting tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
48
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 46 publications
(52 citation statements)
references
References 37 publications
(42 reference statements)
4
48
0
Order By: Relevance
“…Ambipolar light‐emitting transistors (LETs) represent multifunctional architectures which integrate switching characteristic (property of transistors) and light emission capacity (nature of LEDs) into a unitary device . In ambipolar LETs, electrons and holes can be injected from source–drain electrodes to gate‐tunable semiconducting channel and then recombine with each other to emit light with specific wavelength .…”
Section: Functional Applications Of Ambipolar Transistorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Ambipolar light‐emitting transistors (LETs) represent multifunctional architectures which integrate switching characteristic (property of transistors) and light emission capacity (nature of LEDs) into a unitary device . In ambipolar LETs, electrons and holes can be injected from source–drain electrodes to gate‐tunable semiconducting channel and then recombine with each other to emit light with specific wavelength .…”
Section: Functional Applications Of Ambipolar Transistorsmentioning
confidence: 99%
“…In addition, Gwinner et al reported ambipolar LETs possessing larger EQE of more than 8% and higher luminance efficiency exceeding 28 cd A −1 via tuning light outcoupling of transistors utilizing polymeric semiconducting poly(9,9‐dioctylfluorenealt‐benzothiadiazole) (F8BT) (Figure c,d) . Furthermore, photonic crystals are also utilized in ambipolar LETs to improve their optoelectronic performance . Natali et al fabricated transparent ambipolar LETs which exploited multilayer high‐capacitance photonic crystal (ZrO 2 /Al 2 O 3 ) as blocking dielectric .…”
Section: Functional Applications Of Ambipolar Transistorsmentioning
confidence: 99%
“…It is thus possible to optimize charge transport and cavity properties independently from each other. However, rather than trying to create a feedback cavity for lasing or changing the emissive properties via weak coupling, the focus here is on strong light–matter coupling and the electrical creation and manipulation of exciton‐polaritons.…”
Section: Novel Applications Of Lefetsmentioning
confidence: 99%
“…Light emitting thin film transistors (LETFTs) have emerged as a promising candidate for the next‐generation electronics due to the dual integration of switching capacity of a transistor and light emission characteristics of a light emitting diode . This unique characteristic of LETFT enhances its application potential in advanced electronics such as electric pump lasers, display pixels, and optical communications . High carrier mobilities, nature of trap states, and carrier density are vital parameters for fabricating LETFT .…”
Section: Introductionmentioning
confidence: 99%